2020
DOI: 10.1007/s10926-020-09889-9
|View full text |Cite|
|
Sign up to set email alerts
|

Job Crafting Among American Workers with Disabilities

Abstract: Purpose Job crafting is an informal, employee-initiated approach to job re-design that has not been tested among people with disabilities, thus far. The purpose of this study is to examine crafting behaviors of workers with disabilities and individual factors associated with crafting behaviors. Methods We conducted a survey of employees with disabilities who were 18–64 years old and had at least 1 year of work experience. Bivariate and multivariate methods were used to: (1) compare the use of job crafting beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 33 publications
2
38
1
Order By: Relevance
“…Previous studies on job crafting in various firms and organizations have recorded the effects of the participants' background on their job crafting behavior [e.g., 16,18]. In conformation, this study also revealed that demographic background affects the job crafting practice of the participants.…”
Section: Do the Demographic Backgrounds Of The Lecturers Affect Theirsupporting
confidence: 53%
See 2 more Smart Citations
“…Previous studies on job crafting in various firms and organizations have recorded the effects of the participants' background on their job crafting behavior [e.g., 16,18]. In conformation, this study also revealed that demographic background affects the job crafting practice of the participants.…”
Section: Do the Demographic Backgrounds Of The Lecturers Affect Theirsupporting
confidence: 53%
“…Likewise, [15] also found that job crafting has association to work performance. This was echoed by several other studies [e.g., 9,16].…”
Section: Craftingmentioning
confidence: 56%
See 1 more Smart Citation
“…An increasing consensus suggests that well-being should be the core target of governmental policies ( Forgeard et al, 2011 ). This means that governments should focus on improving the subjective outcomes of their citizens (happiness and satisfaction), rather than objective outcomes such as GDP, when determining policy goals.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Many previous studies have explained theoretical perspectives on job wellbeing ( Deci and Ryan, 2008 ; Page and Vella-Brodrick, 2009 ; Fisher, 2014 ; Laine and Rinne, 2015 ). The degree of perceived wellbeing varies with profession and associated stress level, and unique characteristics are associated with perception ( Cai et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%